Unlocking Msme Satisfaction in the Digital Era: A Model of Service Quality, Ease of Use, and Perceived Usefulness - Ulfah Tika Saputri; Meilinda Dwi Anugrah; Kurnia Widya Oktarini; Devi Febrianti; Edy Firza; Zulkifli Zulkifli (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to predict MSME user satisfaction with digital financial reporting, specifically the Akuntansiku application, by integrating the Technology Acceptance Model (TAM) and the Information Systems Success Model. It examines service quality and ease of use as independent variables, with perceived usefulness as a mediating factor influencing user satisfaction. Using a quantitative explanatory design, data were collected from 51 MSMEs in Prabumulih City and analyzed with SEM-PLS. The findings reveal that service quality significantly and positively affects both perceived usefulness and user satisfaction, with perceived usefulness serving as a significant mediator. Conversely, ease of use has no significant impact on perceived usefulness or satisfaction. These results emphasize that service quality and perceived usefulness play a more dominant role in shaping user satisfaction than technical ease of use. Practically, the study underscores the importance of developing digital systems that deliver value and high-quality service to promote sustainable digital adoption among MSMEs.